2014
DOI: 10.1161/circresaha.114.305567
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Cardiovascular Stem Cells

Abstract: 45Human embryonic stem cells have been shown to differentiate to beating cardiomyocytes, SA nodal-like cells and mesodermal Recent Developments in Cardiovascular Research:The goal of "Recent Developments" is to provide a concise but comprehensive overview of new advances in cardiovascular research, which we hope will keep our readers abreast of recent scientific discoveries and facilitate discussion, interpretation, and integration of the findings. This will enable readers who are not experts in a particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 136 publications
(127 reference statements)
1
28
0
1
Order By: Relevance
“…MSC‐conditioned medium increases capillary density and preserves cardiac function 31. Recent clinical trials have suggested that secretion of paracrine factors may be the underlying mechanism responsible for the improvement in outcomes 4. In this study, we found that epicardial transplantation of MSC‐loaded patch enhances sustained production of Tβ4, HIF‐1α and VEGF by the engrafted cells and infarcted cardiac tissue and is more effective for simulating the epicardium compared with intramyocardial MSC transplantation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…MSC‐conditioned medium increases capillary density and preserves cardiac function 31. Recent clinical trials have suggested that secretion of paracrine factors may be the underlying mechanism responsible for the improvement in outcomes 4. In this study, we found that epicardial transplantation of MSC‐loaded patch enhances sustained production of Tβ4, HIF‐1α and VEGF by the engrafted cells and infarcted cardiac tissue and is more effective for simulating the epicardium compared with intramyocardial MSC transplantation.…”
Section: Discussionmentioning
confidence: 53%
“…Resent preclinical studies and clinical trails have shown that stems cell transplantation may be an effective way to improve cardiac function and attenuate adverse ventricular remodelling of the ischaemic myocardium 3, 4. There are several candidate stem cells for cardiac transplantation that have been recently evaluated 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the mechanisms underlying the beneficial effects of MSCs are not completely understood. In addition, several important questions regarding the delivery method and route, the amount of injected cells, and the timing for stem cell transplantation are among the factors that may limit cell-based therapies in the treatment of ischemic heart disease [9,10,53]. These issues, undoubtedly, require further studies to optimize the cell therapy approaches, and represent a focus of future research in this field [9,10,53].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs therapy is an ongoing approach to repair the heart in preclinical and clinical studies after cardiac events and has brought positive results [8][9][10]. Despite the evidences that MSCs reduce left ventricular dilatation [11], increase vascular density [12,13], decrease the extent of the infarcted area [9,11], reduce the apoptosis, and necrosis of cardiomyocytes [11,14], more consistent results from stem cell therapy in heart diseases may, indeed, be achieved through rigorous clinical trials, amount of cells providing maximal efficiency, optimal time frame for transplant, best procedures to manipulate the cells, and via of administration [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of promoting CPC lineage specification demonstrated in the C-CURE study has fueled exploration of other avenues of in vitro and in vivo lineage specification by biomaterials, cytokines, growth and trophic factors, miRNAs, co-culture and formulation of combinatorial approaches of cell clusters and chimeras [114]. Biomaterials including cardiac-specific cellularized or decelluarized matrices coated with stem cells, growth, trophic and mitotic factors, chemotactic factors or cytokines to facilitate CPC survival, vascularization, migration and serve as reservoirs for delivery of these growth and/ or trophic factors may extend the benefits of cell therapy and afford novel opportunities for tissue re-engineering [124]. There is growing enthusiasm for use of allogeneic stem cells, particularly hypoimmunogenic stem cells such as hMSCs or engineered cells, given ease of procurement, advanced preparation and the generally reduced secretory and proliferative potential of autologous stem cells prepared from patients with acute and chronic heart failure [88,106].…”
Section: Future Directionsmentioning
confidence: 99%